(untitled) (Heritage, 2020)
The research focus of this paper is the chapter “Parabasis” of the polemical book The Anatomy Lesson by Danilo Kiš. The author aims to draw a parallel with the genealogical characteristics of the parabasis in ancient comedy to explain its function in The Anatomy Lesson and to examine the veracity of Kiš’s self-interpretation, and thus the justification of his creative self-consciousness.